Analisis Perilaku Konsumsi Muslim Dalam Berbelanja Skin Care Pada Mahasiswi Di Pamekasan - Wulan sari, Asri; Indrarini, Rachma (Jurnal Ekonomika dan Bisnis Islam, 2021)
The purpose of this study is to see the consumption behavior of Muslims on skin care products through online shopping among female students in Pamekasan. The method used in this study was qualitative descriptive research with phenomenological approach by the aim of analyzing and describing Muslim consumption behavior through online shopping on skin care among female students in Pamekasan. The object chosen was the consumption behavior of Pamekasan female students in online shopping of the skin care products. Sources of data used in this study were primary data and secondary data. The primary data of this study was obtained form interviews with sources and observations in the field. This study also used secondary data in the form of journals, books and other literature related. The data validity test technique used was in the form of triangulation of sources and triangulation of techniques as well as analyzing how to reduce data, present data, and find conclusion. The results of this study showed that the consumption behavior of female students in Pamekasan through online shopping on skin care products is still not in accordance with the correct consumption behavior of Muslims because the consumption is excessive, gives priority to lust, causes redundancy and does not pay attention to halal products.